Processing of Meat With Marination System for Increasing Food Safety and Added Value - ., Nurwantoro; Bintoro, V P; Legowo, A M; Purnomoadi, Agung (Indonesian Animal Sciences Society, 2012)
In broad perspective, meat contains many essential nutrients such as protein, fat, minerals, carbohydrates (minor amount) and water. The existence of these nutrients render meat not only as a nutritious food, but also potential as a media for bacterial growth, so that it needs to be further processed. One of the methods to process meat is by soaking the meat in a marinade solution (marination). There are three treatments that maybe performed on meat in the marination system. The first method is using phosphate salt solution to enhance the water holding capacity. The second method is utilizing the acidic salt solution or organic acids to soften the meat and control the bacteria growth. The third method is using spicy solution that can be combined with sugar, salt (NaCl) and organic acids to improve the physical performance and taste of meat as well as to control the growth of bacteria. It is concluded that marination of meat could increase physical, chemical, microbiological properties and sensory. Key words: Marination, meat, safety